Age and weight at first conception and calving in inter-se Jersey x Kankrej heifers - TRIVEDI, M M; PATEL, J M (The Indian Journal of Animal Reproduction, 2023)
The age and weight at first conception and calving were recorded in 24 inter-se Jersey x Kankrej heifers fed individually for energy and protein requirements as per Sen et al. (1978) feeding standard. The age and weight at first conception were 586.91±0.28 days and 264.00±6.44 kg, respectively. The corresponding values at first calving were 867.65±10.43 days and 341.06±9.02 kg. Significant positive correlations were found between weight at different ages and weight at conception as well as calving and between later two traits too. The results indicated that individual care and standard feeding in inter-se heifers could reduce age at first conception and calving.